Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Mona; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)